Magnetic resonance imaging with perfusion and diffusion in assessment of intra-spinal lesions - Maryam Hamdy Foaad; Mohamed El Rakhawy; Mohamed Mohsen (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background MRI is the imaging modality of choice in detecting and evaluating spinal lesions. However, advanced techniques as diffusion and perfusion studies can help more in differentiation between neoplastic and non-neoplastic lesions. Our study aimed to detect the role of diffusion and T2* perfusion weighted imaging in characterization of different spinal lesions by measuring the relative cerebral blood volume (rCBV) and apparent diffusion coefficient value (ADC) of all lesions, comparing perfusion of lesion in relation to normal cord and detection of diffusion pattern of each lesion by observing its signal intensity at diffusion images and ADC map. Results Fifty patients were included in this study. Twenty-five patients were with non-neoplastic lesions and twenty-five patients were with neoplastic lesions. The cutoff value of rCBV was 1.2 in differentiation between neoplastic and non-neoplastic lesions with 92% sensitivity and 100% specificity. The cutoff value of ADC was 1 in differentiation between neoplastic and non-neoplastic lesions with 56% sensitivity and 80% specificity. Conclusions Diffusion and perfusion weighted images help in differentiation between neoplastic and non-neoplastic spinal lesions.